Effects of anti-oxidative and cholesterol lowering capacities of selected edible-medicinal mushrooms towards amelioration of alzheimer’s disease / Mohammad Azizur Rahman - Mohammad Azizur , Rahman (2017)
Alzheimer’s disease (AD) is a neuro-degenerative disorder affecting mainly the elderly people. Though more than 40 million people are suffering from AD complications up to present date, there is hardly any treatment effective in withstanding the progression of AD. Thus, demand for natural, safe and cost-effective AD therapeutics has got momentum. Oxidative stress (OS) and increased plasma cholesterol levels have been implicated among the numerous pathomechanistic factors of AD. Despite some discrepencies, strategies aimed at lowering OS and hypercholesterolemia seems promising as AD therapeutics. Mushrooms have been highly hailed for providing numerous health benefits including anti-oxidative and hypocholesterolemic potentialities. However, combined anti-oxidative and hypocholesterolemic effect of edible-medicinal mushrooms have not been reported though these two aspects have been studied separately. Also, as an AD therapeutic agent, mushroom has not been interpreted through their anti-oxidative and hypocholesterolemic properties. Thus, the present study has been designed to elucidate the anti-oxidative, hypocholesterolemic and AD ameliorating properties of the selected edible-medicinal mushrooms: H. erinaceus, L. edodes, F. velutipes and G. lucidum. Five solvent-solvent partitioned fractions (methanol:dichloromethane, dichloromethane, hexane, ethylacetate, aqueous and hot water extract (HWE) of each of the four mushroom species were screened through in vitro anti-oxidant tests including 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, Folin-Ciocalteu assay, lipid peroxidation (LPO) and low density lipo-protein (LDL) oxidation inhibition tests. Among all, the HWE of G. lucidum had been found possessing the best in vitro anti-oxidative capacity and highest content of polyphenols, tri-terpenoids and sterols. Thus, this mushroom extract had been chosen for the rest of the studies. In vivo anti-oxidative and hypocholesterolemic studies upon rats showed increasing effect towards plasma and liver anti-oxidant enzymes (catalase, glutathione peroxidase and superoxide dismutase) while total cholesterol (TC), triacylglycerol (TG), LDL-cholesterol were decreased and HDL-cholesterol was increasd. This mushroom extract demonstrated absence of adverse effect upon the organ function tests. As derangement of memory and learning abilities is the most notable complication associated with AD, the effect of the HWE of G. lucidum had been tested upon the AD model rats. Feeding of HWE of G. lucidum was found to improve memory and learning abilities of the AD rats. This cognitive improvement has been supported by elevated levels of memory related neurotransmitters in the respective rats. Transmission electron microscopic (TEM) studies demonstrated pronged neuronal dendrites in the G. lucidum HWE treated rats than those of the non-treated. Finally, brain comparative proteomics have identified differentially expressed proteins involved in neurotransmission, metabolism, cellular stress response and misfolding repairment. Improved functional network had been observed among the proteome of the G. lucidum HWE treated rats through STRING analysis. Ingenuity pathway analysis (IPA) identified nervous system development, cell-cell signaling and interaction, molecular transport and cell death and survival among the top-most functional networks among the experimental subjects. Thus, AD ameliorating effect of G. lucidum through anti-oxidative and hypocholesterolemic performances might be implicated in AD therapeutics.